Ethics and the contemporary technique: Implications on health environment - Santos Falcón, Gladys (2005)
Following the thinking of some authors, this paper has the purpose to stimulate health professionals both reflection and discussion on daily practice implications of technical advances and the role of ethics as regulator of these advances. We also wish to analyse changes in the relations between professionals and health services persons/clients, from the point of view of biotechnology. We propose this analysis in order to incorporate in our daily practice ethics for life, liberty for better living, honoring both nature and human dignity.